Pengaruh Micro Influencers Terhadap Customer Online Engagement - Egidya Wyanda; Popy Rufaidah (Jurnal Ilmu Manajemen, 2025)
This study aims to investigate the influence of micro influencers on customer online engagement by examining key dimensions that define influencer effectiveness. Specifically, the research evaluates two main dimensions of micro influencers: Influencer Attractiveness (IA) and Follower Self-Assessment (Emotional Attachment), and their influence on three components of customer online engagement: Cognition, Affection, and Activation. A quantitative method was employed using SEM-PLS approach to test the proposed hypotheses. A total of 232 responses were collected through an online survey distributed to social media users who engage with micro influencer content. The analysis reveals that both Influencer Attractiveness and Emotional Attachment have a significant and positive impact on customer cognitive, affective, and active engagement. These findings highlight the strategic importance of selecting micro influencers who not only appeal visually but also build emotional connections with their audience. The study provides practical insights for marketers to strengthen their digital campaigns by leveraging emotionally resonant and attractive micro influencers to enhance brand engagement.